Foodservice hygiene factors — the consumer perspective. - Ungku Zainal Abidin, Ungku Fatimah; Boo, Huey Chern; Sambasivan, Murali; Salleh, Rosli (Elsevier, 2011)
Food safety is important to today’s food industry operators as consumers have become increasingly concerned about risks related to food. Unlike foodservice operators or health inspectors, consumers can only rely on the visible cues, particularly those associated with food hygiene to judge the level of food safety in eating establishments. While previous research highlighted the influence of foodservice hygiene perception on consumer dining out decision, study examining the constructs of food safety cues that consumers employed is scant. This research aims to bridge the gap by exploring the topic from the consumer perspective. Results indicate that foodservice hygiene is one of the top three considerations when consumers select a dining place. Results of confirmatory factor analysis reveal a four-factor model encompasses staff and handling, food and location, premise and practices, and scent aspects. Further substantiation in different settings is needed for generalization purpose.